O ensino da clínica ampliada na atençao priméria à saúde: percepções e vivências de alunos de graduação médica - Godoy, Daniele Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Many medical schools worldwide have sought to redirect professional education with the purpose to cause an impact on the correction of some of the problems in the current technological medicine. These institutions have been encouraged to change towards teaching procedures that will value care provision quality and the humanization of practices. In Brazil, after the creation of the Unified Public Health System (SUS), medical schools have been provoked to adapt to the needs of the system. Curricular guidelines and the inductive role played by the Ministries of Health and Education, in face of different programs for support to the restructuration of professional education in health care, were some of the elements of support to such processes of change. Among the strategies proposed and adopted is the earlier exposure of medical students to patients, patients’ relatives and communities. In this perspective, in 2002, the Botucatu School of Medicine created the University, Services and Community Interaction Program (IUSC), which is managed by students attending the three first years of the Undergraduate Medical Program, in teaching-learning scenarios in the community. The field of this study was the IUSC III course taught to third-year students in the medical program. The main activity in this course is the performance of supervised medical consultation which is guided by the conceptualizations of humanization and integrality. One of the evaluation strategies in the course is the recording of the activities performed, including its difficult and easy aspects, as well as of reflections, on a field diary produced by students. By basing on such diary as a documental source, this investigation sought to understand students’ experiences and perceptions of the course, to identify, describe and analyze the main topics addressed and, finally, to analyze the diary as a potential instrument to evaluate students´education. It is a qualitative ...

Muitas escolas médicas no mundo têm buscado reorientar a formação profissional na expectativa de impactar na correção de alguns dos problemas da atual medicina tecnológica. Estas instituições têm sido estimuladas a transformarem-se na direção de um ensino que valorize a qualidade da assistência e a humanização das práticas. No Brasil após a criação do Sistema Único de Saúde (SUS) as escolas médicas têm sido provocadas a adaptar-se às necessidades deste último. As diretrizes curriculares e o papel indutivo dos Ministérios da Saúde e Educação, mediante diferentes programas de apoio a reestruturação da formação profissional na saúde, foram um dos elementos de incentivo a tais processos de mudança. Dentre as estratégias propostas e adotadas está a exposição mais precoce dos estudantes de medicina à pacientes, familiares e comunidades. Nesta perspectiva, a Faculdade de Medicina de Botucatu, criou, em 2002, o Programa de Interação Universidade, Serviços e Comunidade, IUSC, dirigido aos alunos dos três primeiros anos de graduação médica, em cenários de ensino – aprendizagem junto à comunidade. Este estudo tomou como campo a disciplina IUSC III ministrada aos alunos do 3º ano médico que tem como atividade principal a realização de consulta médica supervisionada e orientada pelas concepções de humanização e integralidade. A disciplina tem como uma de suas estratégias de avaliação, o registro pelo aluno das atividades realizadas, com suas dificuldades, facilidades e reflexões, em diário de campo. Tendo este diário do aluno como fonte documental, esta investigação buscou compreender as vivências e percepções dos alunos sobre a disciplina, identificar, descrever e analisar os principais temas tratados e, por fim, analisar o diário como potencial instrumento de avaliação formativa do aluno. Trata-se de um estudo de natureza qualitativa, documental, esta investigação buscou ...
Keywords: Educação medica; Cuidados primários de saúde; Ensino superior; Avaliação educacional; Pesquisa qualitativa; Primary health care